MON-321 Metastatic Melanoma with Unknown Primary Site in a Patient with Multiple Endocrine Neoplasia Type 1 - Kamilaris, Crystal (J Endocr Soc, 2019)
Background: MEN1 is a rare hereditary tumor syndrome caused by germline inactivating mutations of the tumor suppressor gene MEN1 and is characterized by a predisposition to endocrine tumors primarily of parathyroid, enteropancreatic, and anterior pituitary origin, as well as nonendocrine neoplasms. Cutaneous manifestations mainly include lipomas, angiofibromas, and collagenomas. Melanoma has been observed in MEN1 with 9 cases described in the literature, including 2 cases with unknown primary site (Nord et al. 2000; Baldauf et al. 2009; Brown et al. 2015). Clinical Case: A 45 year old man with MEN1 syndrome manifesting as primary hyperparathyroidism, metastatic pancreatic neuroendocrine tumor (NET), Zollinger-Ellison syndrome, nonfunctional pituitary microadenoma, anterior mediastinal mass and skin angiofibromas presented with a left neck mass that developed over 1 year. CT neck confirmed a 2.2 cm left lateral neck level V mass. Further evaluation revealed stable NET disease with the exception of an enlarging 1.3 cm anterior mediastinal nodule. (18)F-FDG PET/CT demonstrated more activity in the left neck mass and mediastinal mass than (68)Ga-DOTATATE PET/CT. Biopsy of the left neck mass revealed a high grade malignant neoplasm with epithelioid features and markedly elevated MIB1. Tumor cells were positive for CD56, SOX-10 and S-100 protein, but negative for CD20, CD3, CD5, chromogranin, synaptophysin, AE1/AE3, CAM5.2, C-Kit and p53. Molecular analysis showed pathogenic variants in BRAF, TERT, PIK3C, and RB1, a likely pathogenic variant in FBXW7, and a variant of uncertain significance in PMS2. Given these histologic and molecular findings, the diagnosis of metastatic melanoma was favored. Ophthalmological evaluation, skin examination and biopsy of suspicious cutaneous lesions did not reveal the primary site of melanoma. PCR did not reveal MEN1 loss of heterozygosity (LOH) of the neck mass, though there was insufficient material to evaluate for large MEN1 deletions. Conclusion: Of the 9 cases of melanoma previously reported in MEN1, only 1 was evaluated for MEN1 LOH, which was not demonstrated. MEN1 LOH has been described in sporadic melanoma and in vitro and in vivo studies in mice suggest a role for MEN1 as a tumor suppressor gene in melanoma (Gao et al. 2011, Fang et al. 2013). Whether melanoma in MEN1 is related to the germline MEN1 mutation or is sporadic is still unclear. Evaluation of melanomas for MEN1 LOH initially with targeted sequencing of the germline mutation followed by LOH for markers in and near the MEN1 gene at 11q13, may help further elucidate the role of MEN1 in melanoma.